Establishment of an animal model for monkeypox virus infection in dormice - Gaojie Song; Lingling Cheng; Jun Liu; Yu Zhou; Cuiling Zhang; Yuping Zong (Scientific Reports)
Abstract This study aims to establish an animal model of monkeypox virus (MPXV) infection in dormice through intranasal inoculation. Male dormice aged 4–5 months were selected as experimental subjects and administered different titers of MPXV (103.5 PFU, 104.5 PFU, and 105.5 PFU, respectively) via nasal instillation. Within 14 days post-infection, clinical indicators such as survival rate, body weight changes, respiratory status, and mental state were continuously monitored. Additionally, tissue samples from the lungs, liver, spleen, and trachea of dormice from each group were collected on the 5th and 10th days for virus titer detection, and histopathological analysis was performed on lung samples collected on the 5th and 10th days. Dormice infected with MPXV exhibited typical symptoms such as appetite loss, continuous body weight reduction, aggravated respiratory difficulties, accompanied by lethargy, chills, and other clinical manifestations similar to human monkeypox infection. Virological tests further confirmed the distribution of MPXV in multiple vital organs of dormice, including the lungs, liver, spleen, and trachea, with particularly significant pathological damage observed in lung tissue. An MPXV infection model in dormice was successfully established through intranasal inoculation with a titer of 105.5 PFU MPXV, which can be used for studying the infection mechanism and pharmacology of MPXV.